Improvement of catalytic activity of activated bentonite clay by treatment with cetyltrimethylammonium bromide - Ворончак, Тарас Осипович; Никулишин, Ірена Євгенівна; Піх, Зорян Григорович; Рипка, Ганна Мирославівна; Гнатів, Зоряна Ярославівна (Eastern-European Journal of Enterprise Technologies, 2014)
It was found that treatment of activated bentonite clay (ABC) with cetyltrimethylammonium bromide (CTAB) allows to reduce the average particle size due to the partial stratification of sheet aluminum silicate. Thus, the available specific surface area increases, and, therefore, the number of active centers, which can be involved in chemical reactions grows. Using the activated bentonite clay during cooligomerizing the mixture, which models the composition of C9 fraction of liquid pyrolysis products of diesel fuel in the raw state and after treatment with surfactant showed that the surfactant catalyst treatment allows to increase significantly the cooligomer yield. However, the positive effect of this treatment is observed only when the CTAB/ABC ratio value is less than 0.2, and 0.1 can be considered as the optimum ratio. When using too many surfactants, the cooligomer yield falls despite the increase in the available specific surface area and becomes equal to zero at the CTAB/ABC ratio ≥ 0,3. This phenomenon is most likely caused by deactivation of active centers of catalyst by the surfactant residues, molecules of which are able to react with the indicated centers. This technique can be used for improving the catalytic activity of other catalysts of clay nature, which can be used not only in cooligomerization processes, but also in other reactions, which use acid-base catalysis.